Endotoxin and Cytokines Removal with Adsorption Device in a Child with Sepsis After Transplantectomy (Case Report) - A. A. Eremenko; T. V. Marchenko; V. V. Nikoda; A. K. Zokoev; D. A. Skripalenko (Общая реаниматология)
Sepsis is one of the leading causes of death in kidney transplant recipients.We present our experience of effective removal of bacterial endotoxins and endogenous inflammatory mediators using a multimodal hemosorbent in sepsis, caused by gram-negative polyresistant Klebsiella spp. including K. pneumoniae. The device was used in a 15 y.o. patient after treatment failure of graft-bed abscess and removal of kidney transplant.Results. Two 24-hour sorption procedures on Days 3 and 5 post-transplantectomy in combination with renal replacement therapy resulted in consistent decrease of pro-inflammatory markers concentrations (procalcitonin — 15.111.47.2 ng/ml; C-reactive protein — 23419990 mg/l), preventing therefore further progression of multiple organ dysfunctions.Conclusion. Inclusion of selective adsorption of cytokines and/or lipopolysaccharides into multimodal intensive therapy in an immunosuppressed pediatric patient with sepsis caused by resistant microorganisms improved treatment outcomes.